ChemInform Abstract: Palladium‐Catalyzed ortho‐Acylation of N‐Nitrosoanilines with α‐Oxocarboxylic Acids: A Convenient Method to Synthesize N‐Nitroso Ketones and Indazoles. Issue 39 (September 2016) - Zhang, Liang; Wang, Zhe; Guo, Peiyu; Sun, Wei; Li, Ya‐Min; Sun, Meng; Hua, Chengwen
Abstract: Various N‐Nitroso ketones are prepared by decarboxylative ortho‐acylation of N‐Nitroso compounds with α‐oxocarboxylic acids involving a N atom‐directed activation of C—H bonds.